Voting and Political Participation in the Aftermath of the HIV/AIDS Epidemic - Hani Mansour; Daniel I. Rees; James Reeves (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This is the first study to examine the effect of experiencing a widespread, deadly epidemic on voting behavior. Using data on elections to the U.S House of Representatives and leveraging cross-district variation in HIV/AIDS mortality during the period 1983-1987, we document the effects of the HIV/AIDS epidemic on votes received by Democratic and Republican candidates. Beginning with the 1994 elections, there is a strong, positive association between HIV/AIDS mortality and the vote share received by Democratic candidates. Congressional districts that bore the brunt of the HIV/AIDS epidemic also saw substantial increases in Democratic voter turnout and contributions made to Democratic candidates.
Keywords: D72; I18; 330; HIV/AIDS; epidemic; Democratic; Republican